STRATEGI PEMBENTUKAN KARAKTER KEWIRAUSAHAAN PESERTA DIDIK DI SMKN 1 GOWA - Nasir (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2025)
The formation of entrepreneurial character is one of the important focuses in vocational education to prepare students to face the world of work and become independent entrepreneurs. SMKN 1 Gowa as one of the vocational schools in Gowa Regency has implemented various learning strategies to foster entrepreneurial character in students. This study aims to describe and analyze the strategies for forming entrepreneurial character applied at SMKN 1 Gowa. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the strategies applied include project-based learning, direct practice in student business units, and integration of entrepreneurial values in learning activities. This strategy has been proven to be able to foster an independent, creative, responsible, and confident attitude in students. This study recommends that schools continue to strengthen hands-on experience-based entrepreneurial learning practices and increase collaboration with external parties to enrich students' learning experiences.